Numerical simulation of convective heat losses in a helical tube of a cylindrical solar receiver - Arrif, Toufik; Benchabane, Adel; Chehhat, Abdelmadjid; Belaid, Abdelfetah; Rouag, Amar (Journal of Applied Engineering Science & Technology, 2018)
In this paper, natural convection heat losses in a cylindrical solar receiver are investigated numerically. The study is conducted using three helical tube diameters: 12mm, 16mm and 25mm. The diameter of the receiver is 0.3 m with an aspect ratio equal to one and three aperture ratios of 1, 0.75 and 0.5. In each case, the receiver tube inside the cylindrical cavity is modelled by a helical spiral similar to those of real systems. The simulations are performed for three inlet temperatures (of 50, 75 and 100°C) and four receiver tilt angles (of 0, 30, 60 and 90 0 ) with a constant mass flow rate of 0.0885 kg/s. The effects of some parameters such as receiver size, boundary conditions, tube diameter, receiver tilt, inlet temperature and opening ratio on convective heat losses and outlet temperature are presented in form of graphs. It has been found that the convective heat losses are reduced by using the adiabatic boundary condition imposed on the half-circumference of the tube. Thus, increasing the helical tube diameter causes an increasing in the convective heat losses. The increasing of the fluid temperature and the opening ratio are found proportional to the increasing of convective heat losses.